Menopausal hormone therapy: a course to improve the effectiveness - A L Unanyan; I S Sidorova; L N Aminova; V A Alimov; A D Nikonets; Yu V Chushkov; A V Shchukina; D V Baburin (Гинекология, 2017)
This publication is devoted to one of the most relevant areas of gynecological practice - menopausal hormone therapy. The information is presented in the form of an analytical review of international studies on the benefits and risks of menopausal hormone therapy. Given the rapid growth in the number of women in middle and middle age, it is extremely important to identify the benefits and risks of menopausal therapy in order to optimize the quality of life and long-term well-being.